Removal of Chromium (vi) Ions from Polluted Water Using Kaolinite Supported Fe/Al Oxide(hydroxide) Composite Nanoadsorbents - Fisseha A. Bezza; Evans M. N. Chirwa (Chemical Engineering Transactions, 2022)
Hexavalent chromium (Cr (VI)) contamination of surface and groundwater has become a major environmental concern owing to the diverse applications of Cr(VI)) in several industries. In the current study kaolinite-supported and size-controlled Fe/Al oxide(oxyhydroxide) nanocomposites (Kaolinite@Fe/Al nanocomposites) were synthesized for efficient removal of Cr(VI) from aqueous solution. Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) analysis of the nanocomposites revealed that the nanocomposites were uniformly dispersed, with an average particle size of ~ 25 nm. Batch adsorption studies were carried out to study the effect of (Kaolinite@Fe/Al nanocomposites) on the removal of chromium (VI) from 100 mg/L Cr(VI) contaminated water over a wide pH range (3–10) at various adsorbent dosages. The result demonstrated that the nanocomposites’ adsorption efficiency increased with increasing adsorbent dosage. When the Kaolinite@Fe/Al nanocomposites dosage was increased from 1.0 to 3.0 g/L, the Cr(VI) removal percentage increased from 65.4 % to ~99.0 %. This is due to the greater surface area and availability of more adsorption sites at higher dosages of the adsorbent. There was a significant removal of Cr(VI) in the pH range 3–6 reaching up to 99.0% Cr(VI) removal, however, removal efficiency decreased drastically beyond pH 6. Chromium (VI) exists as CrO42-, HCrO4- and Cr2O72- oxyanionic species while the surface of the adsorbent becomes highly protonated, owing to the variable surface charge imparted by Al/Fe oxides/hydroxides favouring remarkable uptake of Cr(VI) in the anionic form. The experimental data fitted Langmuir adsorption model well with a maximum adsorption capacity of 70.71 mg/g. The results of the study demonstrate that Kaolinite@Fe/Al nanocomposites may have a promising potential for remediation of Cr(VI) contaminated wastewater and industrial effluents.